2019
DOI: 10.1093/annonc/mdy462
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of time-to-event outcomes in randomized trials: an online randomized experiment

Abstract: BackgroundMultiple features in the presentation of randomized controlled trial (RCT) results are known to influence comprehension and interpretation. We aimed to compare interpretation of cancer RCTs with time-to-event outcomes when the reported treatment effect measure is the hazard ratio (HR), difference in restricted mean survival times (RMSTD), or both (HR+RMSTD). We also assessed the prevalence of misinterpretation of the HR.MethodsWe carried out a randomized experiment. We selected 15 cancer RCTs with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…If the RMSTs are reported as complementary to the HR, they would offer a tool to compare the potential of different exposures in similar target populations. 41 This will assist researchers and clinicians in interpreting the impact of such exposures on outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…If the RMSTs are reported as complementary to the HR, they would offer a tool to compare the potential of different exposures in similar target populations. 41 This will assist researchers and clinicians in interpreting the impact of such exposures on outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized experiment, Weir et al 2 demonstrated how clinicians may reach different conclusions when hazard ratios or differences in RMST are reported. Similarly, reporting the difference in RMTL as a complement to subdistribution and cause‐specific hazard ratios may give additional insight to the data and offer a clinically meaningful interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in restricted mean survival times (RMST) has recently become of great interest as an alternative measure of association to the hazard ratio in time-to-event analyses. 1,2 Marginal between-group differences in RMST up to a given timepoint can be estimated nonparametrically by integration of the survival function or, in the presence of covariates, of the inverse probability weighted (IPW) survival function. 3 Moreover, regression models have been introduced to estimate the difference in RMST conditional on covariates.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a critical advantage of the pseudo-observation approach is that the estimates are not sensitive to the assumption of proportional hazards during follow-up, as in Cox proportional hazard regression [25]. RRs and RMST differences are also more easily interpreted by patients and providers than hazard ratios, which could facilitate shared decision-making [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%